The Effect of Health Education Through “ASENTIV” Leaflet Media on The Interest of Woman of Childbearing Age in Performing VIA Tests - Bernadita Widyani; Lumastari Ajeng Wijayanti; Ira Titisari; Dwi Estuning Rahayu; Dewi Marianthi (Journal Keperawatan, 2025)
Background: The incidence of cervical cancer in Indonesia has increased to 2 per 1,000 population. Low early detection rates are a major contributing factor to the rise in cervical cancer cases. This low coverage is influenced by low interest among women of childbearing age, related to a lack of knowledge, perceived health, and fear of the VIA test. The leaflet "Let's Get Early Detection and Get the VIA Test" is designed as an educational tool that provides information on the importance of early cervical cancer detection and is expected to increase interest in early screening. Purpose: To determine changes in the interests of women of childbearing age before and after being given health education using the leaflet “Let's Get Early Detection and Get the VIA Test”. Methods: The study used a pre-experimental method with a one-group pre-test and post-test design. The sample consisted of 40 female respondents of childbearing age (30–50 years old) at the Sukorame Community Health Center in Kediri City, selected using a simple random sampling technique. Data were collected using a modified questionnaire and tested for validity and reliability. Then, data were analyzed using univariate and bivariate analysis with the Wilcoxon signed-rank test to determine differences in interest before and after health education. Results: There was a significant difference in the interest of women of childbearing age before and after being given health education using the leaflet with a p value = 0.008 (p <0.05). Conclusion:  Health education using the leaflet has shown increased interest in VIA screening among women of childbearing age. These results can serve as a basis for community health centers (Puskesmas) to utilize the leaflet as an educational tool to increase participation in early cervical cancer detection.